Minimally invasive therapy in carcinomas of the head and neck - an updated overview - Iro, H... (Radiology and oncology (Ljubljana), 1997)
In this up-to-date review the current role of minimally invasive procedure in head and neck oncology is defined. Endoscopic laser surgery in comparison withcommando procedures is discussed as well as other non-operative treatment modalities, suck as simultaneous chemo-radiotherapy. Special reference is given to the question if functional or radical neck dissection are of the sameoncological value.
Keywords: Drug therapy; Head and neck neoplasms; Laser surgery; Radical neck dissection; Radiotherapy; Surgery; Survival analysis